MANAJEMEN ASUHAN KEBIDANAN INTRANATAL PADA NY”H” DENGAN ANEMIA SEDANG DI RUMAH SAKIT HATIVE PASSO KECAMATAN TELUK AMBON - Dinopawe, Asriaty; Tumidjo, Rasina (Pasapua Health Journal, 2022)
Introduction: Childbirth has a negative impact on the mother and fetus if it is accompanied by complications or problems during pregnancy such as labor with anemia. Anemia can result in prolonged labor in stage I and II which makes the mother lose energy leading to surgery. In addition, anemia also causes retained placenta, secondary postpartum hemorrhage and uterine atony in stage III to stage IV. The aim of implementing Intranatal Midwifery Care Management for Mrs “H” with Moderate Anemia at Hative Passo Hospital in 2020 according to the 7 Steps of Varney and SOAP. Method: case study with Midwifery Management approach according to Varney’s 7 Steps Results: Based on the 7 steps of Varney and SOAP used for the midwifery problem solving process, an assessment has been carried out in the form of monitoring and analyzing data on Mrs. “H” with moderate anemia in labor at Hative Passo Hospital in 2020, the process of labor in stages I to IV took place normally, without complications, the baby was born spontaneously with female sex, the placenta was born with the impression of a complete birth and all the findings and actions that had been carried out on Mrs. “H” were documented with the result that there was no gap between theory and mild cases accompanied by LBW. Conclusion : Management of Midwifery Management in Ny. H with moderate anemia cases have been carried out according to Varney’s 7 Steps and currently the mother is in good condition without postpartum bleeding